ANALISIS PERLINDUNGAN AHLI WARIS MEREK SETIA HATI TERATE BERDASARKAN UNDANG-UNDANG MEREK - Suci Lestari; Simona Bustani (Fakultas Hukum Universitas Trisakti, 2021)
The Legal protection for the heirs of the Setia Hati Terate brands is registered under Law no. 20 of 2016 concerning Brands and Geographical Indications, provides an overview of the suitability of the Supreme Court Judge's decision Number 40K/Pdt.Sus.HKI/2021 with Law No. 20 of 2016 concerning Brands and Geographical Indications. The case is about trademark cancellation requests against brands held by the heirs of the brands. So, the problem in this research explains that basically legal protection for the heirs of trademark rights holders is part of the purpose of the law itself. The research discussion shows that legal protection for trademark rights holders is part of the purpose of the law itself. This type of research is normative and analyzed qualitatively. The opinion of several experts argue that the purpose of law is to protect the interests of the community, and also interprets that the purpose of law is to regulate order in society, and others. The conclusion of this research is in the form of how the legal protection for the heirs of trademark rights holders based on Law no. 20 of 2016 concerning Marks and Geographical Indications.